Aplikasi Berbasis Web untuk Pengelolaan Keuangan Pelayanan Jasa pada Perawatan Kecantikan : Modul Pengeluaran Kas (Studi Kasus di Salon Muslimah, Sumatera Selatan) - Neuron Fachrya, Camelia; Widayanti, Asti; Kastaman, Kastaman (eProceedings of Applied Science, 2023)
Abstract- Salon Muslimah is a service and trading company engaged in the beauty sector. This salon is located in Tanjung Enim, South Sumatra. The services provided are in the form of hair care services, body massages, facial treatments. In carrying out Muslimah salon treatments using herbal and halal products. The management of cash disbursements at this salon is still done manually by recording all transactions in a special book. If this is done continuously, it will cause errors in recording every transaction, for example, there will be errors in writing. In addition, attendance and payroll at this salon are still manual. Therefore, this application was created to assist Muslimah Salons in carrying out daily operational activities. This application uses the Software Development Life Cycle (SDLC) method with a waterfall model, using the MySQL database system and using codeigniter in coding using the PHP programming language. Then the design uses Unified Modeling Language (UML), database design uses Entity Relationship Diagram (ERD), and CodeIgniter framework. This application can handle the problems found in the Muslimah dpm salon and this will produce accounting records such as general journals, ledgers, income statements and balance sheets.Keywords- web-based application, cash disbursement, income statement.